Oceans Odyssey 3 : the deep-sea Tortugas shipwreck, Straits of Florida : a merchant vessel from Spain's 1622 Tierra Firme fleet - Stemm, Greg; Kingsley, Sean (Odyssey marine exploration reports, 2013)
In 1990 Seahawk Deep Ocean Technology of Tampa, Florida, commenced the world's first robotic archaeological excavation of a deep-sea shipwreck south of the Tortugas Islands in the Straits of Florida. At a depth of 405 meters, 16,903 artefacts were recovered using a Remotely-Operated Vehicle. The wreck is interpreted as the Buen Jesús y Nuestra Señora del Rosario, a small Portuguese-built and Spanish-operated merchant vessel from the 1622 Tierra Firme fleet returning to Seville from Venezuela's Pearl Coast when lost in a hurricane. Oceans Odyssey 3 introduces the shipwreck and its artefact coll.